COMPUTER ANALYSIS OF THE THREAD FEEDING SYSTEM USING THE SOFTWARE COMPLEX FOR IMPLEMENTING THE RECURSION ALGORITHM FOR DETERMINING TECHNOLOGICAL LOADS - SHCHERBAN, VOLODYMYR; VOLIANYK, OLEKSII; KOLISKO, OKSANA; MELNIK, GENADIJ; SHCHERBAN, YURYJ (Herald of Khmelnytskyi National University. Technical sciences, 2024)
In the work, on the use of a software complex for the implementation of the recursion algorithm when determining technological loads, a computer analysis of the warp thread supply system in the production of multilayer fabrics was carried out. The values of the current tension in the filling zones of the loom are determined, depending on the shape of the filling line of the main threads, the pre-tension, the material of the guide surfaces, and their shape. As structural elements, guides of large and small curvature with and without radial coverage of the guide were used. The analysis of the thread supply system on the technological equipment allows to determine the change in the relative tension in the filling zones of polyamide complex threads on weaving machines, taking into account the material of the guide, the nature of the interaction of the threads with the guides, taking into account the radial coverage. This makes it possible to improve the technology of manufacturing multi-layer fabrics, which are used for the manufacture of personal property products and tactical equipment of military personnel. In the proposed version of the structure of multilayer technical fabric, there are no warp threads for binding the outer layers of protective and power layers. The connection is carried out by the threads of the base of the outer layers of protection. It has been proven that the structure of the multi-layer technical fabric, the tension of the threads of the base of the outer protective layers, power layers and the threads of the base for binding the outer protective layers and power layers, the size of the overlap, the different stretchability of the gap affect the strength of the surf. The value of the different tension of the loom is provided by the displacement of the rock of the loom relative to the middle line of the elastic system of filling the warp threads on the loom. In order to solve the complex task of assessing the tension of the thread regeneration process on technological equipment, it is necessary to use specialized software complexes to implement the recursion algorithm when determining technological loads. Thus, the topic of this article is relevant, which is important for assessing the intensity of the thread regeneration process in the manufacture of multilayer fabrics based on computer analysis of the thread feeding system using a software complex for the implementation of the recursion algorithm when determining technological loads.